TADEUSZ CZAPCZYŃSKI AS A LITERARY SCHOLAR - Gajak-Toczek, Małgorzata (Prace Polonistyczne, 2022)
The aim of the article is to present the research achievements of Tadeusz Czapczyński. His literary studies centred on many famous writers, including: Hugo Kołłątaj, Aleksander Fredro, Józef Weyssenhoff, Marian Piechal, and Maria Dąbrowska. He went down in the history of literature primarily as a monographer of Maria Konopnicka’s life and artistic oeuvre. What remained central to Czapczyński’s research were his hermeneutic practices. He considered life, with its dynamics, vigour, and spontaneity, the most important research category, as it was the basis of all human activity, including intellectual one. Czapczyński’s observations were scientifically accurate, and the rich bibliography testifies to a thorough examination of the research area. He encrusted his works with numerous quotations, which made it easier for the reader, who did not have access to the sources, to interact directly with the text.